Verifikasi Berita Pada Media Dalam Jaringan Kampus - Wieke Wijayani; Rana Akbari Fitriawan (Dialektika, 2018)
News about the ban on "left" book at Telkom University is the attention of the campus media in the network of Aksara and Daunjati. The book which is the source of information and knowledge of its existence is prohibited, because in the book “left” is considered dangerous by the institution. Each media in preaching an event will be producing a different news, influenced from the framing or framing being used. Framing is done by selecting the issues and a particular aspect through the news, to produce a particular effect from audiences. Campus media must apply the principle of verification so that the news be accurate, objective, poses no slander, gossip, and prejudice. This research aims to find the framing, implementation and verification of the campus online media Aksara and Daunjati in the news ban books "left". The theory used is the principle of news verification and framing analysis Robert N. Entman. This study uses qualitative methods of analysis of the constructivist paradigm using framing. From the results of the research there are similarities on the campus media Aksara and Daunjati in framing the events and causes of the news banning the book "left". Aksara gives more moral to both parties, and Daunjati tends to side with the students. Of the four news that do not provide problem solving to the news, but only one media in one of the news expalins tha solution related to the problem. In the implementation of the principle of verification of the campus media Aksara is transparent. On the campus media Daunjati the addition of sentences on news that does not fit in reality.